Digitalisation of Pesantren through Pegon Keyboard Virtual and Rumah Kitab in Preserving the Archipelago's Khazanah and Islamic Studies - Mamlu’ah, Aya; Rohmawati , Ulva Badi'; Nahdlatul , Ririn Fauziyah; Mahfudoh, Sitti Atiyatul (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2025)
Integrating digital technology into Islamic boarding schools (pesantren) is increasingly essential to preserve and revitalise traditional Islamic education in response to modern pedagogical demands. This study employed a Research and Development (R&D) approach utilising the ADDIE model—analysis, Design, Development, Implementation, and Evaluation—focusing on the initial development phase. The primary objective was to design a digital learning tool that supports using the Pegon script and the broader Islamic intellectual heritage of the archipelago. Data were collected through in-depth interviews with pesantren stakeholders, including ustadz/ustadzah, students (santri), and religious institutional representatives. Feasibility assessments were conducted through expert and practitioner validation using content, language, and visual presentation questionnaires. Qualitative data were analysed through reduction, presentation, and conclusion drawing, while quantitative data were processed using eligibility percentage calculations. The results indicated that the developed virtual Pegon keyboard and rumah kitab (digital book repository) prototypes were categorised as "very feasible" based on expert evaluation. Findings suggest that the successful implementation of digital tools in pesantren requires the pedagogical readiness of educators and students and institutional policy support regarding the use of electronic devices. The digitalisation of pesantren through these applications offers a viable solution to preserving and transmitting Islamic knowledge and local cultural values in both face-to-face and online learning environments. This research contributes to the growing field of digital Islamic education by offering a contextually grounded and culturally sensitive innovation in educational technology design.